A scandal at Stonecliffe - Camp, Candace (Camp, Candace. Stonecliffe novel., 2024)
After the scandal of his broken engagement, Nathan Dunbridge accepted his fate as a bachelor--so of course that's when the most ineligible woman of all turns up in disguise at a society event: Verity Cole, former spy and Stonecliffe's resident troublemaker... a woman Nathan finds equal parts alluring and irritating.